2017
DOI: 10.1007/jhep03(2017)129
|View full text |Cite
|
Sign up to set email alerts
|

Multi-centered AdS3 solutions from Virasoro conformal blocks

Abstract: Abstract:We revisit the construction of multi-centered solutions in three-dimensional anti-de Sitter gravity in the light of the recently discovered connection between particle worldlines and classical Virasoro conformal blocks. We focus on multi-centered solutions which represent the backreaction of point masses moving on helical geodesics in global AdS 3 , and argue that their construction reduces to a problem in Liouville theory on the disk with Zamolodchikov-Zamolodchikov boundary condition. In order to co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
80
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(80 citation statements)
references
References 54 publications
(107 reference statements)
0
80
0
Order By: Relevance
“…Moreover, these problems can be partially addressed by performing explicit analytic calculations [7]. The blocks can also be computed directly from AdS 3 [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these problems can be partially addressed by performing explicit analytic calculations [7]. The blocks can also be computed directly from AdS 3 [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…As rather elegantly proved in [29], this property implies that in general the monodromy matrix M is up to a similarity transformation contained within the group SU(1, 1). Since similarity transformation do not effect the eigenvalues this restricts the eigenvalues of M to be either pure phase or purely real (see figure 3).…”
Section: Jhep08(2018)047mentioning
confidence: 92%
“…As mentioned in a previous section, in [29] it was shown that these constraints imply the reflection symmetry z 2 T (z) = 1 z 2T (1/z). In the following section we will assume that the insertions are evenly distributed around the circle.…”
Section: Jhep08(2018)047mentioning
confidence: 94%
See 2 more Smart Citations